The Effect of Peppermint Essential Oil Administration on Sleep Quality in Asthma Patients of the Manggarai Flores-NTT Tribe - Natul, Fransiska Kurniati; Yona, Sri (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Asthma is a heterogeneous disease, commonly characterized by chronic airway inflammation and symptoms such as wheezing, shortness of breath, chest tightness, and coughing of varying intensity. These symptoms often lead to sleep disturbances at night among asthma patients. Approximately 80% of the global population uses traditional medicine, including essential oils (EO), such as peppermint EO, to address primary health concerns. This study employed a quasi-experimental design with a pretest-posttest control group design. The total sample consisted of 49 respondents, with 25 assigned to the intervention group and 24 to the control group. The results revealed a significant improvement in sleep quality between the pre-test and post-test in the intervention group (p-value = 0.000; α < 0.05), as well as a significant difference in sleep quality between the intervention and control groups post-intervention (p-value = 0.000; α < 0.05). Peppermint essential oil was found to positively influence the sleep quality of asthma patients and can therefore be considered a complementary approach to improving their sleep.